The Cross Ethnic Relationships in Strengthening Social Cohesion in Malaysia - Mak Din, Hairol Anuar; Hassan, Nor Azlili; Noor, Mansor Mohd (IJISH (International Journal of Islamic Studies and Humanities), 2019)
The foundation of developing a nation in Malaysia is based on the integration by which each ethnic identity is maintained and preserved within the Malaysian Federal Constitution. However, there is always a negative perception of the "outsider" on the harmonious condition in Malaysia. This is because they are only influenced by the "talk conflicts" that spreading in the social media as if tomorrow will recur the bloody tragedy of May 13, 1969. Yet, the Institute of Ethnic Studies, Universiti Kebangsaan Malaysia has clarified that Malaysia is now in the era of social cohesion. In this era, the behavior of Malaysians is at the 'everyday-defined' level, where 'they talk conflict, they walk cohesion' and this is a healthy psychosocial behaviour. Hence, in exploring the strengthening level of social cohesion, a survey was conducted on 554 business community from various ethnic groups who had a direct connection to cross ethnic relationships. The objective of this study is to explore the dimensions of cross ethnic relationships experienced by the business community from various ethnic groups; and to study the impacts of cross ethnic relationships towards social cohesion in Malaysia. This article is a sub topic from a study on social mobility among Malaysian business community by specifying on cross ethnic relationships. There are three levels of ethnic relationships, namely; at the individual level, community level and institutional level. The findings found that the cross ethnic relationships among the business community in Malaysia is positive and significant in strengthening the social cohesion in Malaysia.